A kora újkori magyarországi prédikációirodalom kutatásának eredményei és jövőbeni irányai - Kecskeméti, Gábor (Studia Litteraria, 2013)
The research of Early Modern sermon literature in Hungary has achieved significant results in the past decades. The research has covered the availability and interpretation of the texts as well as the historical understanding of the metadiscourse of theoretical reflection on preaching. In my opinion, however, we do not always make a clear enough distinction regarding when and to what extent we deliver the work of a literary historian. This study highlights three approaches based on which we do not simply chase the references of the texts but aim at examining their auto-referential characteristics. 1. Two quite different schools of literary studies have a common interest in understanding the intertextuality of sermon texts. Structural description cannot make a move without intertextuality as it has great significance in judging the structure, formation, integrity, and coherence of texts; while its importance for the approach of reception history is obvious. 2. Regarding all the rhetorical systems of the Early Modern Age, rhetorical genre theory was the one which initiated the greatest renewal of the tradition of rhetorical theory that had stemmed from antiquity and had been revealed by Humanism (Melanchthon’s genus didascalicum; Hyperius’ five homiletic genera). The widespread prevalence of Melanchthon’s idea that had lasted for a century was halted by Vossius’ reception, that is, rational-intellectual teaching-disserting confessional discussion gave its place to the discourse of Classicism at the beginning of the 17th century. Hyperius’ classification was cherished by the homiletics of international Calvinism at the end of the 16th century; it turned his literary genres into those parts of the sermon text that give space to the usus. In the second half of the 17th century, in a Lutheran milieu, provoking emotions got a greater significance – the three non-didactic kinds of Hyperius’ five gains could still provide an appropriate framework to it. 3. Out of the reflections that anticipate the late 18th-century theses of poetic and aesthetic thinking, the theoretic positions occupied by homiletics are the most articulated ones in the field of alterity. In the corpus of previous literature, the text group, which can be most evidently compared to the unique role that emotionality would have in post-romantic literature, had developed in the literary genres of piety.